Concentration and distribution of linear alkylbenzene in sediments of selected Malaysian rivers as molecular markers of sewage treatment efficiency - Sleman Magam, Sami Muhsen (2012)
The present study investigates the distribution of linear alkylbenzenes (LABs) in sediment samples collected from selected locations in Sarawak, Sembulan, and Kuantan rivers in Peninsular Malaysia. Batch studies were conducted to assess the current status of domestic wastes and synthetic detergent pollution in sediments in these three rivers. Twenty-three sampling stations have been selected for sediment collection. Analysis and quantification of LABs was carried out using gas chromatography-mass spectrometry (GC-MS). Concentrations of total LABs in ng/g on a dry weight basis (dw) in the sediment samples of Sarawak River, Sembulan River, and Kuantan River ranged from 156.5 to 7386.2; 643.2 to 5567.1; and 772.8 to 7517.6 ng/g dw, respectively. The I/E ratio (ratio of internal to external isomers of LABs) is employed to estimate the degree of degradation of LABs in aquatic environments, making it a powerful, though simple, tool for monitoring biodegradation of LABs in the environment. The I/E ratios for Sarawak, Sembulan, and Kuantan rivers fell in the ranges 0.52 to 1.24; 0.81 to 1.79; and 0.50 to 1.28,respectively. The I/E ratio at station two in Kuantan River was much lower than those at the other stations, indicating that the sewage discharged into Kuantan River was poorly treated. Anthropogenic activities may contribute to high levels of LABs in sediment samples. In addition to anthropogenic activities, natural features of the sampling location may contribute significant amounts of LAB discharges to the aquatic systems. In sum, the study results demonstrate that the LABs are useful as indicators of pollutants originating from domestic wastes and synthetic detergents.